2020
DOI: 10.3390/antiox9090789
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospection of Natural Sources of Polyphenols with Therapeutic Potential for Redox-Related Diseases

Abstract: Plants are a reservoir of high-value molecules with underexplored biomedical applications. With the aim of identifying novel health-promoting attributes in underexplored natural sources, we scrutinized the diversity of (poly)phenols present within the berries of selected germplasm from cultivated, wild, and underutilized Rubus species. Our strategy combined the application of metabolomics, statistical analysis, and evaluation of (poly)phenols’ bioactivity using a yeast-based discovery platform. We identified s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…The low IC 50 value for Crz1 inhibition by 11β,13-dihydrolactucin suggests that the low absorption rate observed may still provide the potential for modulation of Crz1 activity. The ability of 11β,13-dihydrolactucin to modulate Crz1 activity is very significant and comparable to the well described immunosuppressant drug FK506, known for inhibition of calcineurin and also already described to be active in the yeast system [27].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The low IC 50 value for Crz1 inhibition by 11β,13-dihydrolactucin suggests that the low absorption rate observed may still provide the potential for modulation of Crz1 activity. The ability of 11β,13-dihydrolactucin to modulate Crz1 activity is very significant and comparable to the well described immunosuppressant drug FK506, known for inhibition of calcineurin and also already described to be active in the yeast system [27].…”
Section: Discussionsupporting
confidence: 54%
“…Cells were washed and resuspended in 5 µL of 1,4-Diazabicyclo[2.2.2]octane (DABCO, triethylenediamine) DABCO solution (200 mM DABCO in 75% ( v / v ) glycerol, 25% ( v / v ) PBS) (Sigma-Aldrich). The preparations were monitored for GFP fluorescence as previously described [ 27 ] using a Zeiss Imager Z2 (Zeiss, Germany) fluorescence microscope. Photographs were taken with an Axiocam 506 mono (Zeiss).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, increasing mRNA levels of heme oxygenase 1 (HO-1) and consequently protecting retinal cells from diabetes-induced oxidative stress [ 15 ]. It has also been suggested that differences in polyphenol composition between berry species may account for differences in bioactivity against a range of disorders [ 16 ]. However, anthocyanins are sensitive to physicochemical conditions encountered during gastrointestinal digestion, and may also be modified during absorption and metabolism, leading to structural changes into anthocyanin derivatives with different biochemical properties.…”
Section: Introductionmentioning
confidence: 99%